Análise estrutural do domínio de reconhecimento à carboidrato da lectina de Canavalia brasiliensis e sua relação na indução da produção de óxido nítrico. - Bezerra, Eduardo Henrique Salviano (2011)
Lectins may be defined as proteins of nonimmune origin that have at least one non-catalytic domain that reversibly binds specifically to mono or oligosaccharides. Among plant lectins, legume lectins are the most studied, in particular those lectins belonging to subtribe Diocleinae. The lectins from subtribe Diocleinae show a high degree of similarity in their primary sequence and three-dimensional structure but have different intensities in their biological activities in which they are applied, such as induction of nitric oxide production. The structure of the newly crystallized lectin from Canavalia brasiliensis (ConBr) aims to clarify how these variations are based on the geometry of the residues that comprise the carbohydrate recognition domain (CRD). The lectin from Canavalia brasiliensis was purified and crystallized by vapor diffusion method at 293 K. Suitable crystals were obtained under the condition containing 200 mM sodium chloride, 100 mM HEPES pH 8.5 and 1.8 M ammonium sulfate. The crystals have a space group orthorhombic I222, the unit cell has dimensions a = 68.3 Å, b = 73.0 Å, c = 99.5 Å and angles α = β = γ = 90 ° been observed a monomer in the asymmetric unit with a content of 49.5% solvent. The refinement showed a satisfactory "Rfactor" and "Rfree" of respectively 20.4% and 25.3%. Parameters were determined in the potential of biological activity reported in literature, where the lectin from Canavalia maritima (ConM) has high potential for inducing nitric oxide production compared with the lectin from Canavalia ensiformis (ConA), which has a low potential for induction. Significant differences were found between coordinates of the residues that comprise the CRD of lectins from the subtribe Diocleinae, and comparing these data with potential biological activity was provided a distinct pattern of distances to lectins with high and low potential for induction. The lectin from Canavalia brasiliensis (ConBr) shows a pattern of distances for a great inducer of nitric oxide as ConM, but shows a lower activity than ConA. The distances of CRD explain the difference in activity, but ConBr shown an exceptional case where an assessment of the volume of the site shows a very small site, which explains their discrepancy in biological activity.